2020
DOI: 10.1128/msphere.01056-20
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Role of AcrAB-TolC Efflux Pumps in the Evolution of Antibiotic Resistance Reveals Near-MIC Treatments Facilitate Resistance Acquisition

Abstract: Combatting the rise of antibiotic resistance is a significant challenge. Efflux pumps are an important contributor to drug resistance; they exist across many cell types and can export numerous classes of antibiotics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…In both these studies, the direct effects of the mutations were not determined. 2020) examined the evolution of mutations in E. coli and AcrAB-TolC specifically, respectively, under chloramphenicol growth conditions, and both studies observed the V139F mutation in AcrB-Ec [114,115]. This mutation was also seen by Hoeksema et al (2019) when analyzing the effects of mutations in genes related to AMR, specifically the role of these mutations in the resistance to a second antibiotic after a first antibiotic gave rise to a specific mutation (where V139F was found in strains resistant to tetracycline, which previously acquired resistance to amoxicillin, enrofloxacin or kanamycin) [116].…”
Section: Mutations In Mexy-pa (K79 G287) Increase Aminoglycoside Resistancementioning
confidence: 99%
“…In both these studies, the direct effects of the mutations were not determined. 2020) examined the evolution of mutations in E. coli and AcrAB-TolC specifically, respectively, under chloramphenicol growth conditions, and both studies observed the V139F mutation in AcrB-Ec [114,115]. This mutation was also seen by Hoeksema et al (2019) when analyzing the effects of mutations in genes related to AMR, specifically the role of these mutations in the resistance to a second antibiotic after a first antibiotic gave rise to a specific mutation (where V139F was found in strains resistant to tetracycline, which previously acquired resistance to amoxicillin, enrofloxacin or kanamycin) [116].…”
Section: Mutations In Mexy-pa (K79 G287) Increase Aminoglycoside Resistancementioning
confidence: 99%
“…The basal efflux present in bacterial cells is essentially the first mechanism with membrane impermeability that faces antibiotics in clinical isolates [ 14 , 15 , 16 ]. The basal activity is not clinically detected in a wild strain, although various stimuli are able to quickly initiate their overexpression and synthesis.…”
Section: Clinical Impact Situationmentioning
confidence: 99%
“…Although not detected in routine, the efflux paves the way for the most radical mechanisms of resistance [ 3 ]. A sub-inhibitory intracellular concentration of the antibiotic then promotes the development or acquisition of more specific mechanisms of resistance-like enzymatic responses or target mutations [ 15 , 16 ]. For example, several mutations are found in genes, gyrA and parC , coding the gyrase target and they are frequently associated with efflux resulting in high MIC levels [ 17 ].…”
Section: Clinical Impact Situationmentioning
confidence: 99%
“…AcrB functions as the inner membrane transporter using ATP to enable export, AcrA functions as the membrane fusion protein complexing with the other proteins to generate channels, and TolC functions as the outer membrane protein facilitating efflux outside the cell 85 . In practice, AcrR is a transcriptional repressor which was located upstream of the acrAB operon accounting for the management of this pump system, the deletion of AcrR could facilitate this efflux pump to transport geraniol to span the double-layer membrane into the media 86 .…”
Section: Transporter Engineeringmentioning
confidence: 99%